2022
DOI: 10.1093/tas/txac070
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal antibody preparations from avian origin as a feed additive to beef cattle: ruminal fermentation during the step-up transition diets

Abstract: This study investigated the effects of feeding an avian-derived polyclonal antibody preparation (PAP; CAMAS, Inc.) against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides (40, 35, and 25% of the preparation, respectively) on ruminal fermentation [pH, ammonia-N (NH3-N), lactate, and volatile fatty acids (VFA)] of beef steers during a 21-d step-up diet adaptation. Eight ruminally cannulated Angus crossbred beef steers (658 ± 79 kg of body weight) were assigned in a crossover design to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The rumen pH and N-NH3 concentration have a great impact on the main end products of rumen fermentation, which are the SCFA and the microbial protein, main sources of energy and amino acids for the animal. In this context, when SCFA accumulates and ruminal pH declines, urea cycling is compromised, resulting on a reduced urea infux and N-NH3 concentrations in the rumen ( 37 , 38 ). In the present study, no effect of adaptation period was observed for SCFA concentrations in animals fed only VM.…”
Section: Discussionmentioning
confidence: 99%
“…The rumen pH and N-NH3 concentration have a great impact on the main end products of rumen fermentation, which are the SCFA and the microbial protein, main sources of energy and amino acids for the animal. In this context, when SCFA accumulates and ruminal pH declines, urea cycling is compromised, resulting on a reduced urea infux and N-NH3 concentrations in the rumen ( 37 , 38 ). In the present study, no effect of adaptation period was observed for SCFA concentrations in animals fed only VM.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of polyclonal antibodies has been effective against bovine rotavirus and coronavirus, as well as Salmonella, Staphylococcus , and Pseudomonas (Mine and Kovacs-Nolan, 2002 ). Polyclonal antibodies generated toward Streptococcus bovis and Fusobacterium necrophorum dosed in the rumen decreased the abundance of targeted bacteria as measured by most probable number (MPN) viable cell counts (DiLorenzo et al, 2006 , 2008 ) but had varying effects on dry matter intake, volatile fatty acid concentrations, and rumen pH (Marino et al, 2011 ; Silva et al, 2022a , b ). Avian antibodies have also been investigated to reduce methane produced by ruminal archaea (Cook et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%